2010
DOI: 10.1593/neo.91690
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin Inhibits Non-Small Cell Lung Cancer Growth by a Frizzled 9-Dependent Pathway That Is Blocked by Secreted Frizzled-Related Protein 1

Abstract: The goal of this study was to assess the ability of iloprost, an orally active prostacyclin analog, to inhibit transformed growth of human non-small cell lung cancer (NSCLC) and to define the mechanism of iloprost's tumor suppressive effects. In a panel of NSCLC cell lines, the ability of iloprost to inhibit transformed cell growth was not correlated with the expression of the cell surface receptor for prostacyclin, but instead was correlated with the presence of Frizzled 9 (Fzd 9) and the activation of peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 38 publications
3
59
1
Order By: Relevance
“…Stimulation of NSCLC cells with Wnt7a not only induced the expression of hsa-miR29b but also attenuated NSCLC cell proliferation (Tennis et al, 2010; Winn et al, 2005). To test if the anti-proliferative effects of Wnt7a in NSCLC cells are mediated via the induction of hsa-miR29b, we first stimulated A549 cells with Wnt7a (to induce hsa-miR29b expression), followed by treatment with miR29b precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of NSCLC cells with Wnt7a not only induced the expression of hsa-miR29b but also attenuated NSCLC cell proliferation (Tennis et al, 2010; Winn et al, 2005). To test if the anti-proliferative effects of Wnt7a in NSCLC cells are mediated via the induction of hsa-miR29b, we first stimulated A549 cells with Wnt7a (to induce hsa-miR29b expression), followed by treatment with miR29b precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been shown that a PGI 2 analogue125 can mimic many of the effects of Wnt 7a in the context of Frizzled 9. Recent studies have also shown that the addition of prostacyclin to lung cancer cell lines that have retained Wnt 7a receptor Frizzled 9 results in decreased proliferation, inhibition of anchorage-independent growth,126 and significantly decreases lung cancer growth in vitro.123,126…”
Section: Future Directions For the Treatment Of Lung Cancermentioning
confidence: 99%
“…By preventing platelet aggregation, PGI 2 might also reduce the amount of plateletsecreted VEGF and unwanted angiogenesis [31]. In addition to these platelet-mediated effects, it has been recently shown that PGI 2 can prevent non-small cell lung cancer growth by enhancing frizzled-9 expression and activation of the peroxisome proliferator-activated receptor (PPAR)gamma [32, 33]. Interestingly, this novel PGI 2 /frizzled-9 crosstalk does not correlate with the expression of the cell surface receptor for PGI 2 , suggesting that PGI 2 might exert an anti-tumorigenic activity in a receptor-independent manner.…”
Section: Cox-derived Products In Tumorigenesismentioning
confidence: 99%